EU-ACP economic partnership agreements and ACP integration - Chris Milner; Oliver Morrissey; Evious Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2009)
The direct effects of EPAs on ACP countries arise from the requirement to eliminate tariffs on most imports from the EU. While consumers gain from cheaper imports, the government losses tariff revenue and producers face increased completion, implying adjustment costs. This paper estimates the consumer welfare and revenue impact for a sample of 34 ACP countries of eliminating tariffs on imports from the EU under an EPA, and discusses the associated adjustment costs. Although the ACP overall and on average experiences consumer welfare gains, the gains (or any losses) are small and associated with significant revenue losses and potential adjustment costs. As the gains are associated with increased imports from the EU, larger welfare gains tend to be associated with larger revenue losses and adjustment costs. There is scope for tax substitution to address revenue concerns, but addressing adjustment costs (especially employment) will be much more difficult. ACP countries can exclude up to 20% of imports from the EU from tariff elimination (sensitive products). The paper argues that regionally traded goods should be classified as sensitive and excluded from liberalization. Although this reduces consumer welfare gains (or increases welfare losses), these are likely to be more than offset by the benefits from lower revenue losses and trade effects that reduce adjustment costs. This also serves to encourage increased intra-regional trade: regional exporters gain from the preservation of their regional market share and in all countries domestic producers are likely to produce some regionally traded goods.
Keywords: F14; F15; F17; 330; ACP; EPAs; Imports; Welfare Effects; Integration; Internationale Wirtschaftsbeziehungen; Handelsabkommen; Außenhandelspräferenz; Wohlfahrtsanalyse; EU-Staaten; AKP-Staaten